On the Cauchy Problem for $\mathop {2b}\limits^ →$ -Parabolic Systems with Growing Coefficients - Ivasyshen, S. D.; Pasichnyk, H. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For $\mathop {2b}\limits^ →$ -parabolic dissipative systems and systems with growing coefficients as $| x | → ∞$ in the presence of degeneracies in the initial hyperplane, we investigate the fundamental matrix of solutions and the solvability of the Cauchy problem.